HUBUNGAN BERAT LAHIR DAN STATUS GIZI TERHADAP TINGKAT KECERDASAN INTELEKTUAL (IQ) PADA SISWA SD NEGERI 054901 SIDOMULYO KECAMATAN STABAT KABUPATEN LANGKAT - Destriana Annisa; Albiner Siagian; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Children health and growth is something that really needs to be constantly concerned by many people. Children intellectual and physical development begins since the time they were born and can be affected by the birth weight and nutritional status. This study is designed with a cross sectional which aims to determine the relationship between the birth weights, nutritional status with the students intelligence level in SD Negeri 054901 Sidomulyo, Stabat. The samples are some of the students in grades 1-6 (75 students in total). Birth weight data obtained by giving the questionnaires to the respondents, which are the parents of the students, and the nutritional status of students carried out by anthropometric measurements (BMI/U), while the intelligence level of students measured with Colored Progressive Matrices (CPM) and Standard Progressive Matrices (SPM) IQ test. To analyze the data of the relationship between the birth weight and nutritional status with the intelligence level of the students Chi Square test is used, in which that Cl 95% and the value of α = 0,05. The results shows that from 75 students, 28 students (37,3%) have low birth weight, 26 students (34,7%) have wasting nutritional status, and most students (27 students/36%) have the intelligence level below the average. The data analysis demonstrates an association of birth weight (p=0,0001) and nutritional status (p=0,039) with a level of intelligence. From the analysis, it is concluded that there is a relationship between birth weight, nutritional status and intellectual intelligence level of the students (p=<0,05). This result shows that the children with normal birth weight will have a good intelligence level and the children with better nutritional status will have higher intelligence level. Based on this, it is expected that the school as a facilitator of education can improve the students’ nutrition supervision and services. Keywords: birth weight, nutritional status, intelligence level, school children